MODEL PEMBELAJARAN GUIDED INTERACTION IN TEAM (GIT): INOVASI PENDIDIKAN LINGKUNGAN HIDUP BERBASIS BIOLOGI UNTUK MAHASISWA PGSD - Ichsan, Ilmi Zajuli; Pertiwi, Santhi; Alibowo, Sugi (FKIP Universitas Tanjungpura, 2025)
Environmental education requires new innovations related to the development of learning models. Learning models that need to be developed are those related to interaction skills between groups in environmental education based on biological science. The purpose of this study is to develop a Guided Interaction in Team (GIT) learning model or a guided interaction learning model in a team. The research method used in this study is research and development (R&D) with the Analyze, design, develop, implement, evaluate (ADDIE) approach. The results of this study indicate that the GIT learning model developed has a very valid category so that it is suitable for use in classroom learning. Innovation of learning models is very important to encourage students' skills in interacting in solving environmental problems. Suggestions for future research are to conduct large class trials and implementation of the GIT model in various universities.